Unraveling the Willow Project's Impact on Human Rights: An Inquiry into International Legal Perspectives? - Gunawan, Yordan; Farhansyah, Bagaskara Yonar; Nurhaifa, Reksa Fikri (JURNAL MERCATORIA, 2023)
This article aims to examine human rights violations resulting from the U.S.-led agenda as a national strategic project, specifically the Willow Project. This project is a consequence of Saudi Arabia's participation in multilateral cooperation among developing countries, with Saudi Arabia being the largest oil trading partner and the United States serving as the oil supplier. The focus of the issue centers on the Willow Project, a U.S. drilling initiative conducted in the State of Alaska, with global environmental impacts that infringe upon human rights. The research employs a normative-empirical method, prioritizing international law, encompassing concepts, principles, and doctrines as legal sources to address the legal issues related to human rights violations. The Willow Project influences the United States' policy direction, fulfilling the country's energy needs through oil drilling, thereby affecting global climate change and posing risks to the international community. The substantial carbon emissions generated can contribute to rising Earth temperatures, potentially leading to the emergence of new diseases due to extreme weather conditions.